Still life - Penny, Louise (London : Sphere, 2011)
In a small town in Quebec a women supposedly loved by her community is found in the woods, murdered. Chief Inspector Armand Gamache looks for the small clues which will point him to the killer.
Keywords: Victims of violent crimes -- Fiction; Detective and mystery fiction